Comparisons of the 1995 and 1998 coral bleaching events on the patch reefs of San Salvador Island, Bahamas - McGrath, Thomas A. (2003)
Coral patch reefs around San Salvador Island, Bahamas have been monitored with the aid of Earthwatch volunteers three times a year since 1992. During that period two significant mass bleaching events occurred: autumn 1995, and late summer 1998. Elsewhere in 1995, bleaching was caused by higher-than-normal summer sea tempera-tures; in San Salvador, however, temperatures were normal. In 1998 a prolonged period of higher-than-normal sea temperatures preceded bleaching on San Salvador and worldwide. During the 1995 event, one of the monitored reefs had twice the percentage of coral colonies bleached as the other two. Bleaching was more evenly distributed among the reefs during the 1998 event. In 1995 Agaricia agaricites was significantly more affected than other coral species, with almost 50% of all its colonies showing bleaching. Bleaching was more evenly spread among coral species in 1998, with five species showing bleaching on more than 40% of their colonies. Bleaching began on Millepora as early as August during the 1998 event and progressed to other species through the remainder of the autumn. In 1995 bleaching was not seen until late autumn and appeared to impact all affected species at about the same time. Recovery from the 1995 event was complete: no coral death or damage above normal background levels were seen. In the 1998 event, all Acropora cervicornis on the monitored reefs died and A. palmata was severely damaged. Millepora sp. lost almost half of their live tissue, and Montastraea sp. showed significant tissue damage following this event. Phototransect analysis suggests that more than 20% of total live tissue on affected species died during the 1998 event. A. cervicornis has demonstrated no re-growth from 1998 to 2000 on monitored reefs. Monitoring has suggested sig-nificant differences in causes and courses in these two events.